2019
DOI: 10.1186/s13046-019-1310-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-8 secreted by tumour cells impair the function of NK cells via the STAT3 pathway in oesophageal squamous cell carcinoma

Abstract: Background Recurrence and metastasis are the leading causes of tumour-related death in patients with oesophageal squamous cell carcinoma (ESCC). Tumour-infiltrating natural killer cells (NK cells) display powerful cytotoxicity to tumour cells and play a pivotal role in tumour therapy. However, the phenotype and functional regulation of NK cells in oesophageal squamous cell carcinoma (ESCC) remains largely unknown. Methods Single cell suspensions from blood and tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 59 publications
3
110
0
Order By: Relevance
“…Thus, in the older adult with severe COVID-19, superimposed on a baseline reduction in NKCC and activatory receptor expression would be a SARS-CoV-2 driven induction of functional exhaustion via the up-regulation of NKG2A ( 134 ). Moreover, with in vitro studies having shown that exposure to IL-6 and TNF-α, two cytokines whose circulating levels are elevated in COVID-19 patients ( 3 , 77 , 146 ) impairs NKCC and reduces perforin, NKp30 and NKp46 expression ( 147 149 ), then the SARS-CoV-2-induced cytokine storm would exacerbate the abovementioned functional and phenotypical features of NK cell immunesenescence, which would be predicted to further reduce NK cell anti-viral activity.…”
Section: Pathogen Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the older adult with severe COVID-19, superimposed on a baseline reduction in NKCC and activatory receptor expression would be a SARS-CoV-2 driven induction of functional exhaustion via the up-regulation of NKG2A ( 134 ). Moreover, with in vitro studies having shown that exposure to IL-6 and TNF-α, two cytokines whose circulating levels are elevated in COVID-19 patients ( 3 , 77 , 146 ) impairs NKCC and reduces perforin, NKp30 and NKp46 expression ( 147 149 ), then the SARS-CoV-2-induced cytokine storm would exacerbate the abovementioned functional and phenotypical features of NK cell immunesenescence, which would be predicted to further reduce NK cell anti-viral activity.…”
Section: Pathogen Eliminationmentioning
confidence: 99%
“…However, based on emerging data that suggests excessive pro-inflammatory responses in older adults negatively regulates their immune responses ( 204 , 205 ), we propose the following alternative hypothesis: inflammaging predisposes older adults to severe COVID-19 by suppressing the immune response to SARS-CoV-2 . Whilst in vitro and in vivo studies have demonstrated that exposure to pro-inflammatory cytokines can modulate the phenotype and/or function of innate and adaptive immune cells ( 147 149 , 206 ), it is the work of Akbar et al that have specifically linked hyper-inflammation to impaired antigen specific immune responses during aging. Using a human experimental system that investigates antigen-specific immunity in vivo , the group has consistently demonstrated an age-related impairment in the delayed type hypersensitivity (DTH) response to varicella zoster virus (VSV) antigen ( 204 , 205 , 207 ).…”
Section: Pathogen Eliminationmentioning
confidence: 99%
“…19 In addition, it is noteworthy that IL-6 and IL-8, undergoing an increased release in the early phase of COVID-19 infection, impair the functions of NK cells via STAT3-dependent mechanisms, thus contributing to the reduced cytotoxic capacity of these cells. 20 Since it has been widely acknowledged that various leukocytes, including NK and CD8 + cells, can be engaged in bidirectional cross-talk with neutrophils, it is conceivable that an alteration of both the number and function of these cells can compromise their mutual equilibrium. 21 Indeed, it has been well established that contact-dependent interactions, involving neutrophils and NK cells, can stimulate potently the latter cells to produce interferon (IFN)-γ, a versatile cytokine holding a unique position in the antiviral defense system.…”
mentioning
confidence: 99%
“…1). In parallel, this scenario could be worsened further by the presence of high IL-6 and IL-8 levels, which can enhance the neutrophil infiltration and activity, 23,24 while holding an inhibitory action on NK cells 20 (Fig. 1).…”
mentioning
confidence: 99%
“…And IL-6 or IL-8 secreted by primary ESCC cells impairs the function of NK cells via the STAT3 signaling pathway. 44 Tumor-associated macrophages (TAMs) have been reported to play a crucial role in in ammatory tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%